Age-Based Causes and Clinical Characteristics of Immediate-Type Food Allergy in Korean Children - Jeong, Kyunguk (Allergy Asthma Immunol Res, 2017)
PURPOSE: Age-based causes and clinical characteristics of immediate-type food allergy (FA) have not been sufficiently studied. Therefore, we investigated age-dependent clinical profiles of FA in Korean children through an extensive multicenter investigation. METHODS: Using a case report form developed by the authors, a retrospective medical record review was performed of patients (0-18 years old) diagnosed with immediate-type FA between September 2014 and August 2015 in 14 tertiary hospitals in Korea. RESULTS: A total of 1,353 children and adolescents, 93% younger than 7 years, were enrolled in the present study, and 1,661 cases of immediate-type FA were recorded in these patients. The 7 major causative foods were cow's milk (28.1%), hen's eggs (27.6%), wheat (7.9%), walnuts (7.3%), peanuts (5.3%), buckwheat (1.9%), and shrimps (1.9%). Categorizing the patients into 4 age groups revealed that the most common causative food was different for each age group: cow's milk (<2 years), walnuts (2–6 years), walnuts (7–12 years), and buckwheat (13-18 years). The onset time of symptoms was less than 10 minutes in 49%, between 10 and 30 minutes in 17%, and between 30 minutes and 2 hours in 34% of cases. Food-induced anaphylaxis was reported in 506 (30.5%) out of 1,661 cases, and the 7 major causes of food-induced anaphylaxis was cow's milk (27.5%), hen's eggs (21.9%), wheat (11.3%), walnuts (10.5%), peanuts (5.9%), buckwheat (4.2%), and pine nuts (3.0%). The proportion of anaphylaxis was highest in the patients allergic to buckwheat (67.7%), followed by those allergic to pine nuts (57.7%), walnuts (43.8%), wheat (43.5%), and peanuts (34.1%). CONCLUSIONS: The 5 major causative foods of immediate-type FA in Korean children were cow's milk, hen's eggs, wheat, walnuts, and peanuts. The distribution of causative foods was considerably distinctive according to different age groups. Anaphylaxis was reported in 30.5% of immediate-type FA cases.